Pengaruh Media Sosial Sebagai Sumber Informasi Dalam Pengambilan Keputusan Investor Berinvestasi, Latar Belakang Pendidikan dan Penghasilan Sebagai Variabel Kontrol - Harry Hidayat Kamil; Aries Tanno (Politeknik Ganesha Medan, 2022)
This research is about the influence of social media in Indonesia on investment decision making.Today's social media has grown rapidly and become a source of information by investors.The emergence of corporate social media, investment company social media and stock analyst social media provides investors with diverse information.This study looks at how information dissemination, interactions on social media can affect information asymmetry in investment decision making.This study uses primary data by distributing questionnaires on social media (investment groups, hashtags #shares, #investment and #investment stocks), then 150 samples are taken using purposive sampling method.The result of this research is that the social media of investment companies and stock analysts can reduce information asymmetry in making investment decisions.In contrast to corporate social media, although it can reduce information asymmetry, it does not affect investment decisions.